Spatial variability in the trends in extreme storm surges and weekly-scale high water levels in the eastern Baltic Sea. (1st March 2016) - Soomere, Tarmo; Pindsoo, Katri
Abstract: We address the possibilities of a separation of the overall increasing trend in maximum water levels of semi-enclosed water bodies into associated trends in the heights of local storm surges and basin-scale components of the water level based on recorded and modelled local water level time series. The test area is the Baltic Sea. Sequences of strong storms may substantially increase its water volume and raise the average sea level by almost 1 m for a few weeks. Such events are singled out from the water level time series using a weekly-scale average. The trends in the annual maxima of the weekly average have an almost constant value along the entire eastern Baltic Sea coast for averaging intervals longer than 4 days. Their slopes are 4 cm/decade for 8-day running average and decrease with an increase of the averaging interval. The trends for maxima of local storm surge heights represent almost the entire spatial variability in the water level maxima. Their slopes vary from almost zero for the open Baltic Proper coast up to 5–7 cm/decade in the eastern Gulf of Finland and Gulf of Riga. This pattern suggests that an increase in wind speed in strong storms is unlikely in this area but storm duration may have increased and wind direction may have rotated. Highlights: Baltic Sea water level separated into storm surges and volume of the entire sea. Spatial variations in trends of maxima of both components established. All spatial variations in water level maxima are represented by local storm surges. Rotation of wind direction largely drives the increase in the water level maxima.